2023
DOI: 10.3389/fepid.2023.1137040
|View full text |Cite
|
Sign up to set email alerts
|

Household structure is independently associated with malaria risk in rural Sussundenga, Mozambique

Kelly M. Searle,
Dominique Earland,
Albino Francisco
et al.

Abstract: IntroductionMozambique has the fourth highest malaria cases and malaria mortality globally. Locally, malaria incidence increases from low in the southern region to high in the central and northern regions. Manica Province in central Mozambique has the fourth highest prevalence of malaria out of the 11 provinces, and the highest in the central region of the country. In this area where coverage of interventions has been limited, household level risk factors can be important for understanding the natural history … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…This increased risk could be attributed to various factors, including limited access to healthcare services and preventive measures such as ITNs and IRS [77,87,88]. Most individuals with low SES reside in poorly constructed houses with holes on the wall and unscreened windows associated with increased indoor mosquito bites and significantly increasing their vulnerability to malaria infections [89,90]. Studies have suggested implementing different house modifications to reduce the risk of malaria transmission, including screening windows and doors, repairing walls and using modern roofing materials.…”
Section: The Distribution and Use Of Bed Nets Constitute Core Interve...mentioning
confidence: 99%
“…This increased risk could be attributed to various factors, including limited access to healthcare services and preventive measures such as ITNs and IRS [77,87,88]. Most individuals with low SES reside in poorly constructed houses with holes on the wall and unscreened windows associated with increased indoor mosquito bites and significantly increasing their vulnerability to malaria infections [89,90]. Studies have suggested implementing different house modifications to reduce the risk of malaria transmission, including screening windows and doors, repairing walls and using modern roofing materials.…”
Section: The Distribution and Use Of Bed Nets Constitute Core Interve...mentioning
confidence: 99%